Brain drain and productivity growth: are small states different? - Maurice Schiff; Yanling Wang (Institute for the Study of Labor (IZA), 2008)
This paper examines the impact of North-South trade-related technology diffusion on TFP growth in small and large states in the South. The main findings are: i) TFP growth increases with North-South trade-related technology diffusion, with education, and with the interaction between the two, and it decreases with the emigration of skilled labor (brain drain); ii) these effects are substantially (over three times) larger in small states than in large ones. Small states also exhibit a much higher brain drain level. Consequently, the brain drain generates greater losses in terms of TFP growth both because of its greater sensitivity to the brain drain and because the brain drain is substantially larger in small than in large states.
Keywords: F22; 330; Brain drain; technology diffusion; trade; productivity growth; Produktivität; Wirtschaftswachstum; Brain Drain; Technologietransfer; Landesgröße; Nord-Süd-Beziehungen; Entwicklungsländer